Enhanced photoelectric properties of ZnO nanorods arrays synthesized by controlled sol-gel-assisted hydrothermal method. Issue 1 (10th September 2022) - Liu, Jin; Li, Yadong; Lan, Chao; Long, Yan; Lv, Yuanyuan; Zhang, Zhiyong; Zhang, Weihu; Wang, Anyi; Tian, Feng; Zhao, Wu; Yan, Junfeng
Abstract: ZnO nanorods arrays were synthesized by sol-gel-assisted hydrothermal method adjusting hydrothermal [Zn 2+ ]/[(CH2 )6 N4 ] concentration ratio and study their photoelectric properties. When the concentration ratio of [Zn2+ ]/[(CH2 )6 N4 ] is 1:2.5, ZnO nanorods arrays have the best crystal quality, and the photoelectric performance of that is relatively good with a dark current of 3.98 µA, photocurrent of 1045.77 µA. and photoelectric sensitivity of 262.8. In addition, the photoelectric response rise and fall time of that are 53.6 s and 139.8 s. This research has further improved the photoelectric properties of ZnO nanomaterials and is expected to be applied to various ZnO high-performance photodetectors.